2009
DOI: 10.1136/adc.2008.150250
|View full text |Cite
|
Sign up to set email alerts
|

Two-year follow-up of a randomised trial with repeated antenatal betamethasone

Abstract: A single repeat dose of antenatal BM tended not to influence physical growth or neurodevelopment at 2 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…15 However, the earlier trials with multiple courses of prenatal corticosteroid therapy have now reported 2-year outcomes. [16][17][18] All reported no significant differences in rates of death or major neurodevelopmental difficulties at 2 years of age. One study did note a nonsignificant increase in cerebral palsy in the group exposed to more courses of prenatal corticosteroid therapy, but this was not observed in the other studies.…”
Section: Discussionmentioning
confidence: 96%
“…15 However, the earlier trials with multiple courses of prenatal corticosteroid therapy have now reported 2-year outcomes. [16][17][18] All reported no significant differences in rates of death or major neurodevelopmental difficulties at 2 years of age. One study did note a nonsignificant increase in cerebral palsy in the group exposed to more courses of prenatal corticosteroid therapy, but this was not observed in the other studies.…”
Section: Discussionmentioning
confidence: 96%
“…A magnetic resonance imaging study in human newborns suggested that exposure to repeated courses (Ն2 courses of 24 mg of betamethasone) to mothers at risk of preterm labor was associated with decreased cortical surface complexity (28). The results of postnatal studies of preterm human offspring exposed to repeated courses of antenatal steroids for threatened preterm labor are inconsistent, as a number of studies demonstrated no major untoward effects at 2 years of age (8,29,30), but others demonstrated a higher incidence of cerebral palsy (31), behavioral abnormalities, and/or attention issues (30,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, there was an almost significant association between multiple ANS courses and the risk of cerebral palsy (p = 0.06) [27] . The randomized trials studying the effect of a single repeat course of betamethasone showed a decrease in the risk of RDS, without early growth retardation and no evidence on adverse neurological outcome at the corrected age of two years [28,30,31] . The follow-up studies are not complete yet.…”
Section: Therapies Enhancing Maturity Of Fetuses With Threatened Pretmentioning
confidence: 99%
“…Follow-up studies on the efficacy and safety of repeated ANS are available for the two large trials. There were no significant differences in neurological development or growth during the first 2 years of life [27][28][29] . However, there was an almost significant association between multiple ANS courses and the risk of cerebral palsy (p = 0.06) [27] .…”
Section: Therapies Enhancing Maturity Of Fetuses With Threatened Pretmentioning
confidence: 99%